Volumetric shape making and pattern cutting - Campbell, Lesley (Textile and Design Lab and Colab at Auckland University of Technology, 2014)
This paper, in light of pedagogical observations, seeks to explore and examine an alternative approach to pattern cutting through volumetric shape making and a practical, process led investigation using Alien body shapes as a teaching resource. The holistic fashion designer explores and engages with both silhouette and pattern cutting, by developing the skills of volumetric shape making. The process of pattern cutting and volumetric shape making is an iterative translation between two dimensions and three dimensions which requires a practical, experimental approach. A sequential series of interactive workshops have been developed using irregular shaped mannequins to facilitate and develop this process, promoting creative outcomes and a deeper understanding of pattern cutting. This hands on improvisational approach without a known outcome allows for design to progress organically. The above process of thinking, “drawing” and pattern cutting in three dimensions can be extremely challenging and alien to fashion students who often have a pattern cutting foundation based on technical drawings and drafting principles mostly in a two dimensional format. The aim is to explore whether a synaptic link created between hand, eye and mind through an algorithm, can assist the holistic fashion designer and enhance creativity. The vehicle of delivery for this investigation is a series of experimental workshops undertaken by all three levels of BA (Hons) Fashion Design students at Sheffield Hallam University. This dynamic working method challenges conventional teaching methods of demonstration, books and handouts and promotes enjoyment of the journey, thus reducing preconceived ideals, allowing more scope for spontaneous outcomes. Student workshops also explore morphology as a challenge to the traditional western convention of body contouring through flat pattern cutting. Morphology is explored through a series of irregular shaped, non-humanoid forms: Alien Bodies. Full-scale Alien Body mannequins are provided as a resource in the workshop on which to apply the method of direct working in three dimensions to generate an initial pattern. Reflection, analysis and discussion of the pattern shape when transformed back to the flat plane, aims to promote comprehension and underpin the holistic designing/pattern cutting approach. “Alien Body - Pushing Pattern Parameters” workshops culminated in an exhibition at the Sheffield Institute of Arts Gallery where a selection of 18 garments and their flat patterns, all created by students during the previous six month period, were displayed. This paper evaluates data captured and draws on anecdotal evidence gathered from students attending these workshops as well as looks at the methodologies used including process led investigation and peer review within the university environment. It forms a cornerstone for further questioning of whether the fashion designer and pattern cutter is the same person.
Keywords: Challenging; Volumetric; Conceptual; Holistic; Experimental